The Role of Fertilizer Subsidies in Rice Productivity and Profitability: Evidence from Indonesian Smallholder Farmers - Widyastutik, Widyastutik; Aminah, Mimin; Panjaitan, Dian Verawati; Cahyadi, Eko Ruddy (Signifikan: Jurnal Ilmu Ekonomi, 2026)
Research Originality: This study provides micro-level evidence on the dual effects of fertilizer subsidies on rice farmers’ production and profitability, a dimension rarely examined simultaneously at the household level in Indonesia. Using data from two contrasting rice-producing regions, the study isolates subsidy effects on both physical output and farm profit while controlling for input costs and price conditions. Research Objectives: To analyze the effects of fertilizer subsidies on rice production and farm profit in Karawang (West Java) and Lombok (West Nusa Tenggara). Research Methods: OLS regression was applied to cross-sectional data from 51 rice-farming households. Two models were estimated: a production function and a profit function. Empirical Results: Fertilizer quantity, land size, and labor positively influence rice production. Farm profit is significantly affected by production quantity, rice price, total cost, and pesticide cost. Fertilizer cost is not a significant determinant of profit. Implications: Fertilizer quantity, not cost, drives production. Subsidies should be maintained but reoriented toward targeted, quantity-based schemes and improved distribution efficiency to maximize welfare impact. JEL Classification: Q12, Q18, D24, I32